Upaya Peningkatan Literasi Keuangan Syariah dan Kewirausahaan Halal pada Siswa SMA IT Assalam Martapura melalui Sosialisasi dengan Pendekatan Financial Mindset - Dian May Syifa; Luqyana Puteri Anggraini; Ajeng Juniwanti; Afifah Amini; Hafizoh Zokhairia Lathifa; Nur Ika; Amelia Rahmaniah (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity is motivated by the low level of sharia financial literacy among Generation Z and the rise of risky economic behaviors such as online gambling and illegal online loans in Banjar Regency. The purpose of this activity is to improve the understanding of SMA IT Assalam Martapura students regarding productive and ethical pocket money management through a financial mindset approach based on sharia principles. The method used is Participatory Action Research (PAR) with interactive socialization techniques covering sharia investment, halal business opportunities, and Islamic philanthropy. The results show that the use of attractive visualizations and a digital lifestyle approach effectively triggered enthusiasm and increased students' ethical awareness in identifying financial risks. Despite time constraints, students successfully understood strategies to turn pocket money into blessed future assets. The conclusion of this service is that strengthening sharia financial literacy from an early age is a strategic step to form a financially wise and economically independent younger generation. The importance of these results provides recommendations for schools to integrate sharia financial literacy education into additional curriculum programs sustainably.